PENGARUH PENDEKATAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) PADA PEMBELAJARAN PAI TERHADAP PRESTASI SISWA KELAS 11 SMA NEGERI 1 PONOROGO - Yoga Prima Wandana; Syarifan Nurjan; Muhibuddin Fadhli (International Journal of Learning and Education, 2025)
The integration of technology into Islamic Religious Education (PAI) has become a pressing imperative in the digital era. However, empirical evidence on the effectiveness of the Technological Pedagogical Content Knowledge (TPACK) framework specifically within PAI learning contexts in Indonesian senior high schools remains limited. This study aims to examine the influence of the TPACK approach on student academic achievement in PAI learning at SMA Negeri 1 Ponorogo. A quantitative research design was employed, with data collected through a structured Likert-scale questionnaire administered to 80 students selected from a population of 324 Grade 11 students using the Slovin formula. Validity and reliability of the instrument were confirmed through Pearson correlation and Cronbach’s alpha tests. Data were analyzed using simple linear regression via SPSS 25. The results revealed a significant positive effect of TPACK on student achievement (F = 165.387; Sig. = 0.000 < 0.05), with a coefficient of determination (R² = 0.682), indicating that 68.2% of variance in student achievement is explained by the TPACK approach. These findings confirm that TPACK is a statistically robust predictor of learning outcomes in PAI and provide practical implications for teacher professional development in integrating technology into religious education instruction.